“Nothing to Lose & Everything to Gain”: Louis and Marie de Rosset’s Intimate Friendship with Edward Bulwer Lytton - Koivusalo, Anna (Australasian Journal of Victorian Studies, 2022)
By examining the Victorian novelist Edward Bulwer Lytton’s (1803–73) relationship with Louis (1840–75) and Marie de Rosset (1844–70), this essay gives an insight into Lytton’s final years. The de Rossets, a middle-class couple from North Carolina, fled to Britain during the American Civil War. Their pursuit of status and wealth culminated in an intimate friendship with Lytton. Louis worked as Lytton’s unofficial secretary and agent in the United States. Particularly interesting is the close and affectionate personal relationship between Lytton and Marie, which ended in her death in 1870. Lacking the proper background, connections, and behaviour, the de Rossets were not as successful in social rise as they had hoped. The essay demonstrates how Lytton both supported and satirised their attempt to integrate into British high society and how it inspired his central oeuvres The Coming Race (1871) and The Parisians (1873). By analysing the correspondence of the trio, over 200 letters that have not been studied previously, this article informs scholars of history, literature, and cultural studies.